(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This article revisits the Mental Healthcare Act, 2017 (MHCA 2017) in India, assessing its historical evolution, guiding principles, and impact on patient rights and care quality. Beginning with the colonial-era Indian Lunacy Acts and culminating in the MHCA 2017’s alignment with the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD), the analysis illuminates how legislative reforms have progressively emphasized dignity, autonomy, and equitable access to mental health services. Key provisions of the MHCA 2017—such as rights-based care, safeguards against involuntary admissions, and the decriminalization of suicide—demonstrate a shift toward patient-centered ethics and accountability. Despite this progress, challenges persist, including implementation delays, inadequate infrastructure, and complexities in assessing capacity and treatability.